TNI Strategy in Countering Terrorism: Study of Involvement of Former Terrorist Convicts with TNI in Deradicalization Activities in the TMMD Program - Sidik Wiyono; Alfi Haris Wanto; Milda Istiqomah (Budapest International Research and Critics University, 2022)
Collaboration between actors is needed for deradicalization programs, not only institutional actors (institutions) but actors outside of institutions need to be involved for the deradicalization process as a form of national resilience. This paper discusses the involvement of former terrorist convicts (Napiter) who are the members of the Yayasan Lingkar Perdamaian (YLP) and the TNI (Indonesian Armed Forces) during the effort of deradicalization through the TNI Manunggal Membangun Desa (TMMD) program. This research was conducted with the object of former terrorist convicts by conducting interviews, documentation studies and observations. The analysis of this research with a collaborative governance theory approach with qualitative research methods. From this study it was found that the synergy between TNI and ex-terrorist convicts must be integrated for deradicalization process through the TMMD implementation program so that the national resilience will be realized.